The Effectiveness of Know Want Learn Chart Strategy Combine With Picture on Reading Comprehension - Ambarwati, Putri; Candraloka, Olyvia Revalita (Universitas Muhammadiyah Gresik, 2024)
Reading skill is generally thought of as comprehension and interpreted sentences contained in a text to achieve success in English language learned (ELT), but these skills were considered very difficult to achieve. In fact, there are still low scores due to lack of student motivation. Therefore, the aim of this research was to determine the effectiveness of the Know-Want-Learned Chart strategy combined with picture on students' reading comprehension in English subject descriptive text material. This research employs a quantitative approach with a quasi-experimental design. The sample used in the quasi-experiment included 60 students in class VIII MTs Zumrotul Wildan Jepara used purposive sampling. Data collection used a written test in the form of multiple choices as an instrument. The research results show that KWL chart combined with pictures was effective in improved students' reading comprehension and providing motivation in finding the main idea in descriptive text.